Critical success factors of knowledge management: a review. (20th September 2019) - Mathew, Asish Oommen; Rodrigues, Lewlyn L.R.
The purpose of this paper is to explore, compile and analyse the current literature base of critical success factors (CSFs) of knowledge management (KM) using qualitative research approach. After preliminary survey of articles, 72 research papers were identified for detailed review. CSFs were compiled using content analysis methodology and an inductive coding technique. Two iterations of coding were carried out resulting in the identification of nine generic CSFs of KM. The two of the most highly cited CSFs were KM culture and Human Resource Management (HRM). An analysis of the literature was also carried out to bring forth any existing research gaps. The most significant findings were lack of focussed CSF studies with respect to industries and dearth in research regarding various stake holder perspectives. This comprehensive research provides a base for KM researchers to carry out further research.